From Scriptures to Stone: Is the Third Temple Becoming a Reality? - Rimmsh Fatima; Mansoor Ahmad (Social Science Review Archives, 2025)
The Third Temple has always been a controversial subject. Some believe it is just a myth, some believe it is a conspiracy theory while others consider it a part of their faith. It is often seen that people are worried about demolishing of Al-Aqsa and rebuilding of The Third Temple. It is very important to understand the historical perspective of this issue while keeping in view the faith and believes of every religion.